Innovating Organisational Learning and Development for Sustainable Impact: A South African Context - Musengi, Florence (Digital Repository of Theses - SSBM Geneva, 2025)
Organisations operating in South Africa and other African countries’ quickly transforming economic sphere need to train their workers with advanced abilities, sustain crucial staff, and speed up leader progression. The research explores the transformative effects that come from integrating artificial intelligence (AI) and coaching approaches and knowledge management (KM) strategies on learning and development (L&D) practices across banking, defence, healthcare, and manufacturing industries. A research study based on six African countries, including South Africa and Nigeria, along with Kenya, Ghana, Egypt, and Rwanda, demonstrates how AI learning platforms enable customised training systems, demonstrate practical leadership development methods through coaching investments, and establish sustainable KM systems for knowledge retention. The research involved conducting semi-structured interviews and reviewing documents from HR leaders and L&D professionals, which provided insights into effective and ineffective methods along with supporting explanations. The study demonstrates that combined L&D programs create better workforce involvement, higher productivity, and organisational strength. Implementing integrated L&D solutions faces several remaining obstacles: insufficient funding, lack of senior leader support, and inconsistent technological resources. Specifically, the findings give business leaders tools to address ongoing challenges such as workers not feeling engaged, managers who do not lead well, and groups that work in isolation by using modern tools for training. Using AI, companies can replace out-of-date approaches to training. Coaching and knowledge management help companies address the issues of unagile leadership and forgetting the organisation’s past values. The research provides African industries with direction through its recommendation to transition from compliance-based training toward people-focused strategic development, which activates learning as an innovative and competitive driver for long-term business expansion. Keywords: Learning and Development, Artificial Intelligence, Coaching, Knowledge Management, Africa, Human Resources, Talent Development.